The impact of engineered cobalt, iron, nickel and silver nanoparticles on soil bacterial diversity under field conditions - Vishal Shah; Daniel Collins; Virginia K Walker; Shreya Shah (Environmental Research Letters, 2014)
Our understanding of how engineered nanoparticles (NPs) migrate through soil and affect microbial communities is scarce. In the current study we examined how metal NPs, including those from the iron triad (iron, cobalt and nickel), moved through pots of soil maintained under winter field conditions for 50 days, when mesophilic bacteria may not be dividing. Based on total metal analysis, cobalt and nickel were localized in the top layer of soil, even after exposure to high precipitation and freeze–thaw cycles. In contrast, a bimodal distribution of silver was observed. Due to high endogenous levels of iron, the migration pattern of these NPs could not be determined. Pyrosequence analysis of the bacterial communities revealed that there was no significant engineered NP-mediated decline in microbial richness. However, analysis of individual genera showed that Sphingomonas and Lysobacter were represented by fewer sequences in horizons containing elevated metal levels whereas there was an increase in the numbers of Flavobacterium and Niastella . Collectively, the results indicate that along with the differential migration behavior of NPs in the soil matrix, their impact on soil bacterial diversity appears to be dependent on environmental parameters.